PENYULUHAN HUKUM OPTIMALISASI UPAYA PENCEGAHAN KENAKALAN DAN KRIMINALITAS ANAK - Apriyanto; Lusia Sulastri; Dwi Atmoko (Abdi Bhara, 2023)
The community service carried out with the themeOptimizing Efforts to Prevent Delinquency and Crime ofChildren which was carried out at SMK Bina Karya MandiriBekasi, West Java which was aimed at students who were stillteenagers aimed to provide an understanding of juveniledelinquency and criminality that may be committed by teenagers,this is related by preventing this from happening. The methodused in this counseling is by way of lectures and discussions andthen ends with a question and answer. The results obtained fromthis community service are that students and teachers are moresensitive to legal issues, especially those related to juveniledelinquency today. In addition, it is hoped that with thiscommunity service, parents, especially those with teenagechildren, will pay more attention to and supervise activities thatare considered deviant. Because adolescence is a transitionalperiod between children and adults, at this time there is alsodoubt about the role to be played. A teenager is no longer a childand also not an adult. Teenagers begin to try to act and behavelike adults, for example smoking, drinking, using drugs, andengaging in sexual acts. This action is not in accordance with thenorms or rules that apply in society.